Childhood Adversity and the Creative Experience in Adult Professional Performing Artists - Thomson, Paula; Jaque, S. V. (Frontiers in Psychology, 2018)
Childhood adversity is identified as any exposure to abuse, neglect or family dysfunction. Greater exposure to childhood adversity has been strongly identified with increased morbidity and mortality. The aim of this study was to examine differences in creative experiences, fantasy proneness, dispositional flow, exposure to adult traumatic events, and psychopathology (internalized shame, trait anxiety), amongst professional performing artists who experienced no childhood adversity, some adversity, or substantial adversity. This cross-section IRB approved study examined 234 professional performers (dancers, opera singers, actors, directors, musicians). Self-report measurements were included to examine the following psychological factors: adverse childhood experiences (ACE), experience of creativity questionnaire, dispositional flow, trait anxiety, internalized shame, fantasy, and total adult and childhood traumatic events. The sample was divided into three groups based on ACE scores: 0 ACE (n = 93), 1 – 3 ACEs (n = 95), ≥ 4 ACEs (n = 42). The MANCOVA (with age and gender as covariates) results revealed no significant (p = .280) differences between all three ACE groups for the nine flow scales (optimal performance measurements). Performing artists with ≥ 4 ACEs had significantly stronger creative experiences (p = .006) related to distinct creative processing, absorption, and a transformational sense of self and the world. They were also more fantasy prone, shame-based, anxious, and experienced more cumulative past traumatic events (p < .001). Although the high ACE group experienced greater negative effects, they also endorsed positive creative performance experiences.